Experimental study of a mesoscale combustor-powered thermoelectric generator - Hanming Gao; Guoneng Li; Wei Ji; Dongya Zhu; Youqu Zheng; Feixing Ye; Wenwen Guo (Energy Reports, 2020)
Small-scale power sources should be developed with the rapid development of portable electronic equipments. This study presents a mesoscale combustor-powered thermoelectric generator (MCP-TEG). The MCP-TEG generates an electric power of 1.88 W with an overall efficiency of 1.74% at a substantial low hot-end temperature of 95 °C. The relationship among overall, combustion, heat collection and thermoelectric (TE) efficiencies was firstly established in this work. Detailed analysis reveals that the gap between the overall and TE efficiencies is mainly determined by combustion and heat collection efficiencies, and heat collection efficiency is closely related to the residence time of flue gases and preheating design of reactants. The obtained heat collection efficiency is larger than 77.4%, which augments the ratio of overall efficiency to TE efficiency reaching 75.3%, indicating that the present MCP-TEG is well designed. The state of the art of MCP-TEGs is partially revealed, indicating that the ratio of overall efficiency to TE efficiency is an effective metrics to evaluate the performance of various MCP-TEGs.
Keywords: 330; Heat collection efficiency; Mesoscale combustor-powered thermoelectric generator; Residence time